Simulation and implementation of nonlinear control systems for mineral processes - Kam, Kiew M. (Curtin University, 2000)
Differential geometric nonlinear control of a multiple stage evaporator system of the liquor burning facility associated with the Bayer process for alumina production at Alcoa Wagerup alumina refinery, Western Australia was investigated.Mathematical models for differential geometric analysis and nonlinear controller synthesis for the evaporator system were developed. Two models, that were structurally different from each other, were used in the thesis for simulation studies. Geometric nonlinear control structure, consisting of nonlinear state feedback control laws and multi-loop single-input single-output proportional-integral controllers, were designed for the industrial evaporator system. The superiority of the geometric nonlinear control structure for regulatory control of the evaporator system was successfully demonstrated through computer simulations and real-time simulator implementation. The implementation trial has verified the practicality and feasibility of these type of controllers. It also re-solved some practical issues of the geometric nonlinear control structure for industrial control applications. In addition, the implementation trial also established a closer link between the academic nonlinear control theory and the industrial control practices.Geometric nonlinear output feedback controller, consisting of the geometric nonlinear control structure and reduce-order observer was proposed for actual plant implementation on the evaporator system on-site. Its superior performance was verified through computer simulations, but its feasibility on the evaporator system on-site has yet to be investigated either through simulator implementation or actual plant implementation. This investigation was not performed due to the time constraint on the preparation of this thesis and the inavailability of the plant personnel required for this implementation.Robust nonlinear control structures that are simple and computationally efficient have been proposed for enhancing the performance of geometric nonlinear controllers in the presence of plant/model mismatch and/or external disturbances. The robust nonlinear control structures are based on model error compensation methods. Robustness properties of the proposed robust nonlinear control structures on the evaporator system were investigated through computer simulations and the results indicated improved performance over the implemented geometric nonlinear controller in terms of model uncertainty and disturbance reductions.A software package was developed in MAPLE computing environment for the analysis of nonlinear processes and the design of geometric nonlinear controllers. This developed symbolic package is useful for obtaining fast and exact solutions for the analysis and design of nonlinear control systems. Procedures were also developed to simulate the geometric nonlinear control systems. It was found that MAPLE, while it is superior for the analyses and designs, is not viable for simulations of nonlinear control systems. This was due to limitation of MAPLE on the physical, or virtual, memory management. The use of both symbolic and numeric computation for solutions of nonlinear control system analysis, design and simulation is recommended.To sum up, geometric nonlinear controllers have been designed for an industrial multiple stage evaporator system and their simplicity, practicality, feasibility and superiority for industrial control practices have been demonstrated either through computer simulations or real-time implementation. It is hoped that the insights provided in this thesis will encourage more industry-based projects in nonlinear control, and thereby assist in closing the widening gap between academic nonlinear control theory and industrial control practice.Keywords: geometric nonlinear control, input-output linearization, multiple stage evaporator, robust geometric nonlinear control, control performance enhancement.